The Legal Certainty of Digital Consent In The Formation of Electronic Contracts is Reviewed From The Principle of Consensualism - Taqwanda Aulia Mahfud; Subekti Subekti; Yoyok Ucuk Suyono; Ernu Widodo (Dinasti Research, 2026)
The development of information technology has driven a transformation in the formation of contracts from conventional forms to electronic contracts based on digital consent (digital consent). This condition raises legal problems regarding the conformity of digital consent with the principle of consensualism as the basis for the birth of an agreement and its legal certainty in the Indonesian legal system. This study aims to analyze the relevance of the principle of consensualism in the formation of electronic contracts based on digital consent and examine the legal certainty provided to the parties in electronic transactions. This study uses a normative juridical method with a statutory approach, a conceptual approach, and a comparative approach. Legal materials are obtained through literature studies that are analyzed qualitatively and prescriptively. The results of the study show that digital consent in principle has fulfilled the elements of agreement as required in the principle of consensualism because it is a manifestation of the will of the parties expressed through electronic media. However, the current legal arrangements do not provide clear parameters regarding the standard of validity of digital consents, the quality of the agreement, and the mechanism of proof. Therefore, it is necessary to strengthen regulations through the implementation of affirmative consent standards, more specific regulations on forms of digital consent, and increased legal protection for parties to realize legal certainty in the formation of electronic contracts in Indonesia.